Do International Remittances Alleviate or Aggravate Poverty in Developing Countries? - Moises Neil V. Seriño; Therese C. Ratilla (Review of Socio-Economic Research and Development Studies, 2018)
This study investigates the effect of surging increase in international remittances on poverty level in developing countries controlling for income, inequality, and other sources of external funding. Using the newly suggested remittance variable, the method of panel data analysis was applied across 66 developing countries for 9 panel years from 1981 to 2005. Results suggest that international remittances helped in alleviating poverty in developing countries as manifested by the significant negative relationship of remittances on dimensions of poverty such as level, depth and severity of poverty using the methods of pooled ordinary least square method. However, the significance of this alleviating effect of remittances vanishes when using panel data approach suggesting that the alleviating effect of remittances on poverty is less apparent in developing countries when controlling for individual country specific effect.